Ultrasensitive Determination of Malathion in Apples by Aptamer-Based Resonance Scattering. (25th September 2020) - Lai, Xiaoxia; Zhang, Sizhe; Du, Guorong; Wang, Yuxian; Han, Yang; Ye, Nengsheng; Xiang, Yuhong
Abstract: Malathion is a toxic organophosphorus pesticide. When ingested by humans, it affects the nervous system and endangers health. Herein, a new type of aptamer-based sensor was developed for its determination. The results demonstrate that this sensor has high sensitivity and good selectivity and was successfully used for the determination of malathion in apples. The detection mechanism is as follows. The aptamer is adsorbed on the surface of gold nanoparticles (AuNPs) to prevent the aggregation of AuNPs in a high salt solution. After adding malathion, the aptamer specifically binds to malathion and is removed from the surface of the AuNPs. The quantity of aptamer adsorbed on the surface of AuNPs had a negative relationship with the malathion concentration. The unmodified AuNPs aggregated to different degrees in NaCl solution. In the Fehling reaction, various degrees of aggregated AuNPs catalyze the reduction to different size Cu2 O and exhibit different resonance scattering intensities. An excellent linear response between the resonance scattering spectra intensity and malathion concentration was obtained. The limit of detection of the developed method was 5.24 ng/L (15.86 pM). The recovery and repeatability for the apple samples were satisfactory.